A new species of Anilios (Scolecophidia: Typhlopidae) from Central Australia - Shea, Glenn M. (Zootaxa, 2015)
Anilios fossor sp. nov. is described from a single specimen collected in 1989 from Ruby Gap Nature Park, Northern Territory. The species differs from all other Anilios species in the combination of 20 midbody scales, 514 dorsal scales, a rounded, non-angulate snout in lateral and dorsal profile, a nasal cleft contacting the second supralabial and not extending to the head dorsum, and a large round rostral shield in dorsal view. It is unclear whether the paucity of material of this species represents a limited distribution, or poor sampling in a remote, sparsely settled part of the continent. Evidence for the recognition of the Australian typhlopid fauna as a distinct genus Anilios is critically reviewed, and the genus is found to be recognizable only on genetic evidence. Some other recent nomenclatural and taxonomic changes in the Australian typhlopid fauna are considered and rejected.